Individual Brain Metabolic Connectome Indicator Based on Jensen-Shannon Divergence Similarity Estimation Predicts Seizure Outcomes of Temporal Lobe Epilepsy - Zhu, Zehua; Zhang, Zhimin; Gao, Xin; Feng, Li; Chen, Dengming; Yang, Zhiquan; Hu, Shuo (Frontiers in Cell and Developmental Biology, 2022)
Objective: We aimed to use an individual metabolic connectome method, the Jensen-Shannon Divergence Similarity Estimation (JSSE), to characterize the aberrant connectivity patterns and topological alterations of the individual-level brain metabolic connectome and predict the long-term surgical outcomes in temporal lobe epilepsy (TLE). Methods: A total of 128 patients with TLE (63 females, 65 males; 25.07±12.01y) who underwent Positron emission tomography (PET) with 18F-fluorodeoxyglucose (FDG) imaging were enrolled. Patients were classified either as experiencing seizure recurrence (SZR) or seizure free (SZF) at least 1 year after surgery. Each individual's metabolic brain network was ascertained using the proposed JSSE method. We compared the similarity and difference in the JSSE network and its topological measurements between the 2 groups. The 2 groups were then classified by combining the information from connection and topological metrics, which was conducted by the multiple kernel support vector machine. The validation was performed using the nested leave-one-out cross-validation strategy to confirm the performance of the methods. Results: With a median follow-up of 33 months, 50% of patients achieved SZF. No relevant differences in clinical features were found between the 2 groups except age at onset. The proposed JSSE method showed marked degree reductions in IFGoperc.R, ROL.R, IPL.R, and SMG.R; and betweenness reductions in ORBsup.R and IOG.R; meanwhile, it found increases in the degree analysis of CAL.L and PCL.L, and in the betweenness analysis of PreCG.R, IOG.R, PoCG.R, PCL.L and PCL.R. Exploring consensus significant metabolic connections, we observed that the most involved metabolic motor networks were the INS-TPOmid.L, MTG. R-SMG.R, and MTG.R-IPL.R pathways between the 2 groups, and yielded another detailed individual pathological connectivity in the PHG.R-CAU.L, PHG.R-HIP.L, TPOmid.L-LING.R, TPOmid.L-DCG.R, MOG.R-MTG.R, MOG.R-ANG.R, and IPL.R-IFGoperc.L pathways. These aberrant functional network measures exhibited ideal classification performance in predicting SZF individuals from SZR ones at a sensitivity of 75.00%, a specificity of 92.79%, and an accuracy of 83.59%. Conclusions: The JSSE method indicator can identify abnormal brain networks in predicting an individual’s long-term surgical outcome of TLE, thus potentially constituting a clinically applicable imaging biomarker. The results highlight the biological meaning of the estimated individual brain metabolic connectome.